PROBLEMS OF RATIONAL USE AND PROTECTION OF GROUNDWATER WITHIN THE RUSSIAN FEDERATION - Pykhtin, Alexey Ivanovich (Journal of Applied Engineering Science, 2019)
The performed studies have evaluated groundwater resources across continents and hold their comparison with the resources of surface water. Temporary condition of water resources in the world, the prospects for their security of countries are a matter concern. The world situation with water resource is clearly not satisfactory and remains disturbingin general. In many regions there is co-quantitative depletion of water resources, their deficit becomes increasingly stressful. Water availability has decreased approximately in 2 times (from 13 to 7.6 thousand m3/year per person) since 1970. It is given the modern availability of fresh water in Europe. Russia occupies a leading position according to the total volume of freshwater. In Russia as a whole the security of inferred groundwater resources is 6 m3 per day per person. However, it is experienced a significant water shortage in a number of constituent entities of the Russian Federation  due to uneven distribution of groundwater resources. Up to 70% of the total volume of extracted groundwater is used for drinking and general-purpose needs. Water supply of more than 50 % of the territory and population of the Russian Federation is based only on groundwater. There are territories with local water scarcity. Environmental threat is the deterioration and contamination of groundwater under the influence of anthropogenic load. It is recorded about 6 thousand sites of technogenic pollution of groundwater in the country. Also there are about 500 water intakes with constant or episodic pollution of groundwater. Mainly, pollution is evident in urban and industrial agglomerations making it impossible to supply consumers with water of required quality. In accordance with the basic principles of state policy in the field of use and protection of water objects, we have identified the activities that ensure rational use, restoration and protection of groundwater resources.